The Effects of Gamma Irradiation on the Growth and Propagation of In-Vitro Chrysanthemum Shoot Explants (cv. Yellow Puma) - I. Dwimahyani; S. Widiarsih (Atom Indonesia, 2010)
The study on the effect of gamma irradiation on in-vitro shoot growth of chrysanthemum cv. Yellow Puma has been carried out. The aim of the study was to observe genetic variability of shoot growth caused by gamma irradiation. Shoot explants with four leaves were irradiated by gamma with dose of 10, 15 and 20 Gy with 3 replications at each of dose. The irradiated shoot explants were then transferred into fresh MS solid medium and placed in a growth room. Observation was performed on number of leaves and branches on M1V0 generation, while plantlets height and number of branches were observed a M1V1 generation. Number of survival plantlets and multiplication rate on three subsequent subcultures were observed as well. Results showed that gamma rays with dose of 20 Gy inhibited growth of leaves as much as 50% compared to control (shoots without irradiation), and branches 73.7% in three weeks. Observation on multiplication rate at M1V1 generation showed that gamma irradiation with dose of 10 Gy promoted multiplication rate as much as 10% higher than control. It can be concluded that in vitro mutagenesis using gamma iradiation with dose of 10 to 15 Gy can be used for inducing genetic variability of chrysanthemum cv. Yellow Puma. Received: 18 December 2008; Revised: 10 August 2010; Accepted: 30 August 2010